Manajemen Pengaturan Tata Ruang Penyimpanan Obat Puskesmas Batua Kota Makassar - Handayani, Meliana; Jayadilaga, Yadi; Wahyudin; Akbar, Andi Adhayana (PHARMACON, 2025)
This research focus on setting storage space requirements to enable maximum management and management of storage. The study is qualitative research with a case study approach. Researchers act as an instrument to collect information related to the management of drug storage spatial arrangements through in-depth interviews, observation and document review. This research was conducted at the Batua Community Health Center, Makassar City in March – June 2024 with 5 informants, using a purposive sampling technique. Data analysis was carried out using the stages of data reduction, data presentation, drawing conclusions and verification. This research shows that of the 14 indicators proposed, 8 indicators expected the standards while the other 6 indicators were not. The medicine warehouse at the Batua Community Health Center has extensive limitations that affect access and distribution of medicines. Further research is needed to identify more comprehensive drug logistics management to ensure the quality and quality of drugs and maintain the effectiveness of pharmaceutical services.